1971
DOI: 10.1159/000175352
|View full text |Cite
|
Sign up to set email alerts
|

The Concentrations of Fructose, Glucose and Lactate in the Splanchnic Blood Vessels of Rats Absorbing Fructose

Abstract: The concentrations of fructose, glucose and lactate were measured in the hepatic portal vein, hepatic vein and systemic aorta of fed and fasting rats given a large meal of fructose by gastric intubation. The maximum concentration of fructose found in portal vein blood was within the range 20–40 mg/100 ml. The corresponding range in the systemic circulation was 2–6 mg/100 ml. A fractional hepatic fructose uptake of 54.9% and 71.5% was found in fed and fasting rats, respectively. Little fructose was removed by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
2

Year Published

1973
1973
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 13 publications
5
28
0
2
Order By: Relevance
“…In our experiments [unpublished results), we found in peripheral blood (mixed blood from the neck vessels) of rats fed for 3 weeks the fruc tose diet fructose concentrations of 1.7 and 2.2 mg/100 ml in two experimen tal series. Similar concentrations of fructose in the blood were recorded recently by T o p p in g and M ayes [21] in rats after acute administration of fructose. The maximum fructose concentration in their experiments was 20-40 mg/100ml intheportal blood, but only 2-6mg/lOOml in the aortal blood.…”
Section: Discussionsupporting
confidence: 86%
“…In our experiments [unpublished results), we found in peripheral blood (mixed blood from the neck vessels) of rats fed for 3 weeks the fruc tose diet fructose concentrations of 1.7 and 2.2 mg/100 ml in two experimen tal series. Similar concentrations of fructose in the blood were recorded recently by T o p p in g and M ayes [21] in rats after acute administration of fructose. The maximum fructose concentration in their experiments was 20-40 mg/100ml intheportal blood, but only 2-6mg/lOOml in the aortal blood.…”
Section: Discussionsupporting
confidence: 86%
“…Infusion of fructose at this rate has been shown to elicit a steady-state plasma fructose concentration lower than 2.0 mM (28), which is comparable to the concentrations reported in postprandial circulation (29,30) and in our in vitro experiments. A bolus injection of fructose (0.3 g/kg) did not alter plasma glucose or insulin, suggesting that a moderate increase in circulating fructose alone is not sufficient to stimulate insulin release (Fig.…”
Section: Postprandial Concentrations Of Fructose Potentiate Gsis Via supporting
confidence: 86%
“…When ingested by mouth, fructose is initially absorbed by the small intestine and flows through the liver (1). As a consequence of the high rate of extraction of fructose by liver, correspondingly low fructose concentrations are found in systemic blood vessels after meals (11). Several previous studies have examined serum and urinary fructose concentrations in patients with diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…First, impaired fructose metabolism in the liver might play an important role, given that several studies have shown that the liver metabolizes at least half of all fructose (11,13). Second, the transport system for fructose might be disrupted.…”
mentioning
confidence: 99%